A Novel Slicing Strategy to Print Overhangs without Support Material - Michael Wüthrich; Maurus Gubser; Wilfried J. Elspass; Christian Jaeger (Applied Sciences, 2021)
Fused deposition modeling (FDM) 3D printers commonly need support material to print overhangs. A previously developed 4-axis printing process based on an orthogonal kinematic, an additional rotational axis around the z-axis and a 45° tilted nozzle can print overhangs up to 100° without support material. With this approach, the layers are in a conical shape and no longer parallel to the printing plane; therefore, a new slicer strategy is necessary to generate the paths. This paper describes a slicing algorithm compatible with this 4-axis printing kinematics. The presented slicing strategy is a combination of a geometrical transformation with a conventional slicing software and has three basic steps: Transformation of the geometry in the .STL file, path generation with a conventional slicer and back transformation of the G-code. A comparison of conventionally manufactured parts and parts produced with the new process shows the feasibility and initial results in terms of surface quality and dimensional accuracy.